2019
DOI: 10.1142/s0219649219500448
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of User Acceptance of Electronic-HRM through the Extension of UTAUT Model via the Structural Equation Modelling Approach

Abstract: Despite the assured benefits of strategic primacy for HR administrators, performance effectiveness and cost reduction provided by Electronic-Human Resource Management (e-HRM), user acceptance of these systems is a critical factor for the initiative’s success. Accordingly, current research addresses factors that permit or hamper e-HRM adoption in private universities of Jordan. Conceptual theoretical model which extends the proposed UTAUT model was used, self-administered questionnaire was developed and data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
22
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(35 citation statements)
references
References 43 publications
10
22
3
Order By: Relevance
“…This research revealed that EE has an insignificant effect on HR analytics intention to use which opposed the results of previous literature (Venkatesh et al. , 2003) but is following the study of Al-Ajlouni et al. (2020) and Mittal et al.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…This research revealed that EE has an insignificant effect on HR analytics intention to use which opposed the results of previous literature (Venkatesh et al. , 2003) but is following the study of Al-Ajlouni et al. (2020) and Mittal et al.…”
Section: Discussioncontrasting
confidence: 99%
“…This result is consistent with those of previous studies (Vargas, 2015; Tarhini et al. , 2017; Al-Ajlouni et al. , 2020; Tiwari et al.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations